A World Of Field Trips : Going to a Beach - Rebecca Rissman (China Raintree Publisher, 2013)
This book teaches readers about what field trips are, why people take field trips, and what you can learn from a field trip to a beach.
Keywords: Easy Read Nonfiction -- Easy Read Nonfiction